Analisis Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Dan Learning Together (LT) Terhadap Hasil Belajar Siswa Sekolah Dasar (SD) - Nia Fibria Nuriana (Universitas PGRI Adi Buana Surabaya, 2020)
This study aims to determine the student learning outcomes using cooperative learning type Teams Games Tournament (TGT) and Learning Together (LT). This theoretical study is a systematic mapping study or study letarature. Student learning outcomes in the study of this theory are seen from the mathematics learning outcomes of elementary school (SD) students who use the cooperative learning model of the Teams Games Tournament (TGT) and Learning Together (LT) types. The results of the theoretical study show that there are differences in student learning outcomes that use the Teams Games Tournament (TGT) type of cooperative learning model, but they are not significant. While the results of the study of student learning outcomes theory using the cooperative learning model type Learning Together (LT) showed significant similarities. The results of the theoretical study can be concluded that in general student mathematics learning outcomes with the application of cooperative learning models of the Teams Games Tournament (TGT) and Learning Together (LT) experience a significant increase.